HER-2 positivity rate in dogs with mammary carcinoma: a systematic review and meta-analysis - UZABACI, E.; OZYIGIT, M.O.; ERCAN, I.; ARDA, O. (Journal of the Hellenic Veterinary Medical Society, 2020)
Human epidermal growth factor receptor 2 (HER-2) plays an essential role in cell growth and survival. HER-2 overexpression occurs in 20-30% of human breast tumors and has prognostic value as it is associated with disease progression. HER-2 overexpression is also associated with tumor progression and metastasis in malignant mammary tumors of the canine. However, in the literature, different positivity classifications/scoring were used in the evaluation of HER-2 status, and there is no consensus in terms of scoring of HER-2 expression in canine mammary tumors. In this study, it was aimed to estimate the HER-2 positivity rate by evaluating the results of the study using different positivity classifications by meta-analysis. In this context, by using ”HER-2 canine mammary tumor” keywords, Pubmed and Web of Science electronic databases were scanned until February 2019, and a total of 97 related studies were found. However, 20 of these studies were used for the analysis. Two different meta-analyses were performed to evaluate the HER-2 positivity status with “2+ and 3+” and “3+” scores. As a result, HER-2 positivity rates were determined at 25.87% and 25.99% for the studies using “2+ / 3+” scores and “3+” respectively for HER-2 positivity. Therefore, this result suggests that the rate of HER-2 positivity is similar between humans and dogs.